Crystal structures of two hydrogen-bonded compounds of chloranilic acid–ethyleneurea (1/1) and chloranilic acid–hydantoin (1/2) - Gotoh, Kazuma (Acta Crystallogr E Crystallogr Commun, 2018)
The structures of the hydrogen-bonded 1:1 co-crystal of chloranilic acid (systematic name: 2,5-dichloro-3,6-dihydroxy-1,4-benzoquinone) with ethyleneurea (systematic name: imidazolidin-2-one), C(6)H(2)Cl(2)O(4)·C(3)H(6)N(2)O, (I), and the 1:2 co-crystal of chloranilic acid with hydantoin (systematic name: imidazolidine-2,4-dione), C(6)H(2)Cl(2)O(4)·2C(3)H(4)N(2)O(2), (II), have been determined at 180 K. In the crystals of both compounds, the base molecules are in the lactam form and no acid–base interaction involving H-atom transfer is observed. The asymmetric unit of (I) consists of two independent half-molecules of chloranilic acid, with each of the acid molecules lying about an inversion centre, and one ethyleneurea molecule. The asymmetric unit of (II) consists of one half-molecule of chloranilic acid, which lies about an inversion centre, and one hydantoin molecule. In the crystal of (I), the acid and base molecules are linked via O—H⋯O and N—H⋯O hydrogen bonds, forming an undulating sheet structure parallel to the ab plane. In (II), the base molecules form an inversion dimer via a pair of N—H⋯O hydrogen bonds, and the base dimers are further linked through another N—H⋯O hydrogen bond into a layer structure parallel to ([Image: see text]01). The acid molecule and the base molecule are linked via an O—H⋯O hydrogen bond.